Step
*
1
of Lemma
fps-geometric-slice_lemma
.....falsecase..... 
1. X : Type
2. valueall-type(X)
3. eq : EqDecider(X)
4. r : CRng
5. m : ℕ
6. n : ℕ+m + 1
7. g : PowerSeries(X;r)
8. g = [g]_n ∈ PowerSeries(X;r)
9. IsRing(PowerSeries(X;r);λf,g. (f+g);0;λf.-(f);λf,g. (f*g);1)
10. 0 = fps-summation(r;upto(m + 1);k.([(1-g)]_k*[(1÷(1-g))]_m - k)) ∈ PowerSeries(X;r)
11. ¬(m = 0 ∈ ℤ)
⊢ [(1÷(1-g))]_m = ([(1÷(1-g))]_m - n*g) ∈ PowerSeries(X;r)
BY
{ xxx(Thin (-1)
      THEN (Subst' fps-summation(r;upto(m + 1);k.([(1-g)]_k*[(1÷(1-g))]_m - k))
            = (([(1-g)]_0*[(1÷(1-g))]_m - 0)+([(1-g)]_n*[(1÷(1-g))]_m - n))
            ∈ PowerSeries(X;r) -1
            THEN Auto
            )⋅
      )xxx }
1
.....equality..... 
1. X : Type
2. valueall-type(X)
3. eq : EqDecider(X)
4. r : CRng
5. m : ℕ
6. n : ℕ+m + 1
7. g : PowerSeries(X;r)
8. g = [g]_n ∈ PowerSeries(X;r)
9. IsRing(PowerSeries(X;r);λf,g. (f+g);0;λf.-(f);λf,g. (f*g);1)
10. 0 = fps-summation(r;upto(m + 1);k.([(1-g)]_k*[(1÷(1-g))]_m - k)) ∈ PowerSeries(X;r)
⊢ fps-summation(r;upto(m + 1);k.([(1-g)]_k*[(1÷(1-g))]_m - k))
= (([(1-g)]_0*[(1÷(1-g))]_m - 0)+([(1-g)]_n*[(1÷(1-g))]_m - n))
∈ PowerSeries(X;r)
2
1. X : Type
2. valueall-type(X)
3. eq : EqDecider(X)
4. r : CRng
5. m : ℕ
6. n : ℕ+m + 1
7. g : PowerSeries(X;r)
8. g = [g]_n ∈ PowerSeries(X;r)
9. IsRing(PowerSeries(X;r);λf,g. (f+g);0;λf.-(f);λf,g. (f*g);1)
10. 0 = (([(1-g)]_0*[(1÷(1-g))]_m - 0)+([(1-g)]_n*[(1÷(1-g))]_m - n)) ∈ PowerSeries(X;r)
⊢ [(1÷(1-g))]_m = ([(1÷(1-g))]_m - n*g) ∈ PowerSeries(X;r)
Latex:
Latex:
.....falsecase..... 
1.  X  :  Type
2.  valueall-type(X)
3.  eq  :  EqDecider(X)
4.  r  :  CRng
5.  m  :  \mBbbN{}
6.  n  :  \mBbbN{}\msupplus{}m  +  1
7.  g  :  PowerSeries(X;r)
8.  g  =  [g]\_n
9.  IsRing(PowerSeries(X;r);\mlambda{}f,g.  (f+g);0;\mlambda{}f.-(f);\mlambda{}f,g.  (f*g);1)
10.  0  =  fps-summation(r;upto(m  +  1);k.([(1-g)]\_k*[(1\mdiv{}(1-g))]\_m  -  k))
11.  \mneg{}(m  =  0)
\mvdash{}  [(1\mdiv{}(1-g))]\_m  =  ([(1\mdiv{}(1-g))]\_m  -  n*g)
By
Latex:
xxx(Thin  (-1)
        THEN  (Subst'  fps-summation(r;upto(m  +  1);k.([(1-g)]\_k*[(1\mdiv{}(1-g))]\_m  -  k))
                    =  (([(1-g)]\_0*[(1\mdiv{}(1-g))]\_m  -  0)+([(1-g)]\_n*[(1\mdiv{}(1-g))]\_m  -  n))  -1
                    THEN  Auto
                    )\mcdot{}
        )xxx
Home
Index